Experimental studies of the spectral characteristics of a free glow discharge in the wavelength range of 340-440 nm. (December 2020) - Bezverkhnii, N O; Monakhov, N A; Petrenko, M V; Lapushkina, T A; Sakharov, V A; Poniaev, S A; Bobashev, S V
Abstract: Non-equilibrium air plasma generated in free glow discharge is characterized by optical emission spectroscopy techniques in the wavelength range of 340–440 nm. The rotational and vibrational temperature are studied as a function of distance from the electrode, to find out differences in the distribution of plasma parameters along with the discharge axis. In this work, the rotational and the vibrational temperature is determined from rovibrational spectra of second positive N2 system. It is observed that N 2 + / N 2 intensity ratio increases from anode to cathode along the discharge axis.